BAAL/CUP Seminar 2015: The language of money and debt: The view from the ground. (23rd September 2016) - Mooney, Annabelle; Sifaki, Evi
Abstract : On 7 and 8 September 2015, the University of Roehampton hosted a BAAL/Cambridge University Press seminar, which brought together researchers from a wide range of perspectives in terms of their objects of study and modes of investigation.